2015
DOI: 10.1007/s40572-014-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Use in Food Animal Production: Assessing Potential Dietary Exposures and Breast Cancer Risk

Abstract: In recent years, increasing attention has been paid to the role of hormones in breast cancer etiology, following reports that heightened levels of endogenous hormones and exposure to exogenous hormones and other endocrinedisrupting chemicals through food and the environment are associated with increased breast cancer risk. Seven hormone drugs (testosterone propionate, trenbolone acetate, estradiol, zeranol, progesterone, melengestrol acetate, and bovine somatotropin) are approved by the U.S. Food and Drug Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…It is also important to note that for relatively time-invariant covariates like SES factors, if specific time windows of exposure for associations with an outcome are found, this can rule out confounding by time-invariant variables based on negative control exposures principles. 29,5961 Although there are methods that have been proposed to account for unmeasured confounding, 6264 they necessarily make assumptions about the structure of the unmeasured (possibly unknown) confounding. Thus, the possibility of simply eliminating some possible confounding may sometimes be preferable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that for relatively time-invariant covariates like SES factors, if specific time windows of exposure for associations with an outcome are found, this can rule out confounding by time-invariant variables based on negative control exposures principles. 29,5961 Although there are methods that have been proposed to account for unmeasured confounding, 6264 they necessarily make assumptions about the structure of the unmeasured (possibly unknown) confounding. Thus, the possibility of simply eliminating some possible confounding may sometimes be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…traffic patterns, meteorological factors, land use characteristics—to predict outdoor ambient pollutant concentrations at the individual’s residence in a given time window. These methods have been used to examine the effects of air pollution on many different health outcomes including cardiovascular, 24 respiratory, 2527 and neurological effects, 28,29 as well as overall mortality. 30–32 …”
Section: Potential Epidemiologic Advantages Of Proxy Measuresmentioning
confidence: 99%
“…Regarding blood as the tissue of measurement, several studies have shown blood to be a relevant surrogate even when studying diseases that primarily affect other tissues (Davies et al, 2012; Kaminsky et al, 2012; Talens et al, 2010; Waterland et al, 2010). Moreover, blood-derived epigenetic signatures can have utility as prenatal exposure biomarkers, even when blood is not primarily involved in the disease being studied (Ladd-Acosta, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It is of interest as a mediating mechanism in exposure-disease associations, and may also have utility as a biological marker of exposure, even if not mechanistically implicated (Ladd-Acosta, 2015). Several groups have investigated associations between DNAm levels and in utero exposure to tobacco smoke.…”
Section: Introductionmentioning
confidence: 99%
“…By obtaining cardiometabolic risk measures before and after, or at least clearly after, PTSD onset or treatment, the likelihood of reverse causation is minimized. Two of the suggested designs use individuals as their own comparator, thus eliminating possible influence of confounding factors that do not vary within individuals over the study period (Weisskopf et al , 2015). Additionally, two of the designs leverage the randomization to treatment found in most clinical trials to further improve causal inference.…”
Section: New Research Directionsmentioning
confidence: 99%